Smart-seq3 and Smart-seq3xpress single-cell RNA sequencing of bone marrow cells from MDS-RS patients - Moura, Pedro Luis; Hellström-Lindberg, Eva (Karolinska Institutet, 2023)
This dataset consists of Smart-seq3 single-cell RNA sequencing data of purified RS from the bone marrow and peripheral blood of 2 MDS-RS patients; and Smart-seq3xpress single-cell RNA sequencing data of FACS-sorted hematopoietic stem cells (HSC), multipotent progenitors (MPP), megakaryocyte-erythroid progenitors (MEP) and erythroblasts from 1 MDS-RS patient. The objective of this data collection was to assess several parameters on how the bone marrow of MDS-RS patients differs from that of healthy donors.

This dataset includes raw sequencing data in .fastq format, processed count matrices and associated pseudonymized metadata.

Processing: In brief, cells were sorted into 384-well plates containing 3uL Vapor-Lock (Qiagen) and 0.3uL lysis buffer consisting of 0.125 µM OligodT30VN (5'-Biotin-ACGAGCATCAGCAGCATACGAT30VN-3'; IDT) adjusted to reverse transcription (RT), 0.5mM dNTPs/each adjusted to RT volume, 0.1% Triton X-100, 5% PEG8000 adjusted to RT volume, 0.4u RNase Inhibitor (Takara Bio, 40 U/µL). After cell sorting plates were briefly centrifuged before storage at -80C. Before RT, plates were denatured at 72 degrees for 10 min followed by addition of 0.1 µL of RT mix; 25 mM Tris-HCL pH 8.4 (Fischer Scientific), 30mM NaCl (Ambion), 1 mM GTP (Thermo Fisher Scientific), 2.5 mM MgCl2 (Ambion), 8 mM DTT (Thermo Fisher Scientific), 0.25 U/µl RNase Inhibitor (Takara Bio), 0.75 µM Template Switching Oligo (TSO) (5′-Biotin-AGAGACAGATTGCGCAATGNNNNNNNNWWrGrGrG-3′; IDT) and 2 U/µl of Maxima H Minus reverse transcriptase (Thermo Fisher Scientific). Plates were quickly centrifuged after dispensing to ensure merge of lysis and RT volumes. RT was incubated at 42 °C for 90 minutes, followed by ten cycles of 50 °C for 2 minutes and 42 °C for 2 minutes. After RT, 0.6 µL PCR mix was dispensed to each well containing the following; 1× SeqAmp PCR buffer (Takara Bio), 0.025 U/µl of SeqAmp polymerase (Takara Bio) and 0.5 µM Smartseq3 forward and reverse primer. Plates were quickly spun down before being incubated as follows: 1 minute at 95 °C for initial denaturation, 14 cycles of 10 seconds at 98 °C, 30 seconds at 65 °C and 2–6 minutes at 68 °C. Final elongation was performed for 10 minutes at 72 °C.

The dataset consists of 2 folders:
- SS3_FACS_PB-BM_RS
- SS3xpress_FACS_HSC_MPP_MEP_EB

The folder SS3_FACS_PB-BM_RS contains 1 rds file, 3 txt files, and 1 compressed folder (tar.gz) with fastq files.
The folder SS3xpress_FACS_HSC_MPP_MEP_EB contains 1 rds file, 7 txt files, and 2 GNU zipped fastq files.

The documentation file File_list_SS3_SS3xpress.txt contains a full list of the files in the dataset.

Syftet med denna datainsamling var att bedöma flera parametrar om hur benmärgen hos MDS-RS-patienter skiljer sig från den hos friska donatorer. Denna datauppsättning består av Smart-seq3 och Smart-seq3xpress singel-cell RNA sekvensering av benmärgsceller från MDS-RS patienter. Se den engelska beskrivningen för mer information.

Datasetet består av 2 mappar:
- SS3_FACS_PB-BM_RS
- SS3xpress_FACS_HSC_MPP_MEP_EB

Mappen SS3_FACS_PB-BM_RS innehåller 1 rds-fil, 3 txt-filer och 1 komprimerad mapp (tar.gz) med fastq-filer.
Mappen SS3xpress_FACS_HSC_MPP_MEP_EB innehåller 1 rds fil, 7 txt-filer och 2 GNU-zippade fastq-filer.

Dokumentationsfilen File_list_SS3_SS3xpress.txt innehåller en lista över datasetets alla filer.
Smart-seq3 och Smart-seq3xpress singel-cell RNA sekvensering av benmärgsceller från MDS-RS patienter
Keywords: Myelodysplastic Syndromes; Myelodysplastiskt syndrom; myelodysplastic syndromes; myelodysplastiska syndrom; sf3b1; sf3b1; mds-rs; mds-rs; Natural Sciences; Naturvetenskap; Biological Sciences; Biologi; Cell Biology; Cellbiologi; Genetics and Genomics; Genetik och genomik; Bioinformatics and Computational Biology; Bioinformatik och beräkningsbiologi; Hematology; Hematologi; Basic Cancer Research; Basal cancerforskning